Bunium serdengectii (Apiaceae), a new species from South Anatolia, Turkey - Duran, Ahmet; Kljuykov, Eugene; Degtjareva, Galina; Samigullin, Tahir; Lyskov, Dmitry (Phytotaxa, 2024)
A new species, Bunium serdengectii (Apiaceae), is described from South Anatolia, Turkey. It grows in open Pinus brutia forests and in macchia formation of the Taurus Mountains in the district of Akseki (Antalya province). The taxonomic affinities of the new species were determined by analyzing morphological data and a molecular phylogenetic study of nrITS. Bunium serdengectii belongs to the section Elegantia, and is related to B. pinnatifolium, but morphologically is more related to B. sayae. The anatomical structure of the fruit is given in detail. The diagnostic morphological characters of B. serdengectii are discussed. In addition, the geographical distribution of the new species and the morphologically related species is mapped.